Keragaman Genetik Kultivar Pisang Diploid (AA) Koleksi Cibinong Science Center Berdasarkan Marka RAPD dan ISSR - Poerba, Yuyu Suryasari; Ahmad, Fajarudin (Universitas Atma Jaya Yogyakarta, 2010)
The banana (Musa acuminata Colla) is considered as an important crop plant due to its high economic value which also has good dietary source. Here, the genetic variation of 20 diploid (AA) banana cultivars from Cibinong Science Center collection were analyzed. Random amplified polymorphic DNAs (RAPDs) and Inter Simple Sequence Repeats fingerprinting of these banana cultivars were carried out by four primers of RPDSs and two primers of inter simple sequence repeats (ISSRs) led to DNA amplification. The amplification products of RPADs and ISSRs were polymorphic, 97.83% and 95%, respectively. Size of the bands was varied from 350bp to 2.0 kbp. The range of genetic distance was from 0.06 to 0.07. The molecular data showed that these banana varieties were diverse collection.